Topical sodium metabisulfite for the treatment of calcinosis cutis: a promising new therapy. (17th April 2016) - del Barrio‐Díaz, P.; Moll‐Manzur, C.; Álvarez‐Veliz, S.; Vera‐Kellet, C.
Abstract : What's already known about this topic? Calcinosis cutis is a chronic calcium‐mediated disease that causes significant morbidity for patients. Multiple treatments have been tried, many of them with varying results and side‐effects. To date, no standard treatment has been generally accepted. What does this study add? Topical sodium metabisulfite is a new, inexpensive emerging therapy that should be considered as a valid alternative treatment in patients with calcinosis cutis, especially in countries where topical sodium thiosulfate is not available. Summary: Calcinosis cutis is a chronic calcium‐mediated disease that causes significant morbidity. Multiple treatments have been tried, with varying results; indeed, to date, no standard treatment has been generally accepted. Sodium metabisulfite is an inorganic compound that, when it reacts with oxygen, becomes sodium sulfate, a metabolite of sodium thiosulfate that has a similar ability to inhibit calcium oxalate agglomeration. Four women diagnosed with calcinosis cutis, secondary to dermatomyositis, systemic sclerosis and radiodermatitis after breast cancer, were evaluated for their response to topical 25% sodium metabisulfite. In all patients a decrease in lesion size, erythema and pain from injuries was shown, with complete resolution of the associated ulcers. One patient had a complete response. None experienced adverse effects. Topical sodium metabisulfite is a promising emerging therapy that should be considered as a valid alternative treatment in calcinosis cutis. Randomized prospective studies are required to evaluate its true efficacy.